(untitled) - Davis, Leonard G. (Boston)
The new edition of this popular book emphasizes the decisions that need to be made to select one procedure over another in the everyday workings of the molecular biology laboratory. Trouble-shooting problems that may emerge when performing such methods are included. New section on the preparation and analysis of differential cDNA libraries
Keywords: Molecular biology,Sinh học phân tử